Molecular Imaging of Expression of Vascular Endothelial Growth Factor a (VEGF A) in Femoral Bone Grafts Transplanted into Living Mice. Issue 7 (July 2014) - Strachna, Olga; Torrecilla, Daniel; Reumann, Marie K.; Serganova, Inna; Kim, Jihye; Gieschler, Simone; Boskey, Adele L.; Blasberg, Ronald G.; Mayer-Kuckuk, Philipp
The biology of cells transplanted with bone grafts is incompletely understood. Focusing on the early angiogenic response postgrafting, we report a mouse femur graft model in which grafts were derived from mice transgenic for a firefly luciferase (FLuc) bioluminescence reporter gene driven by a promoter for the angiogenic signaling molecule vascular endothelial growth factor (VEGF). Upon transplantation into wild-type (wt) mice, in vivo bioluminescence imaging (BLI) permitted longitudinal visualization and measurements of VEGF promoter activity in the transplanted graft cells and demonstrated a lag period of 7 days posttransplantation prior to robust induction of the promoter. To determine cellular mediators of VEGF induction in graft bone, primary graft-derived osteoblastic cells (GDOsts) were characterized. In vitro BLI on GDOsts showed hypoxia-induced VEGF expression and that this induction depended on PI3K signaling and, to a lesser degree, on the MEK pathway. This transcriptional regulation correlated with VEGF protein production and was validated in GDOsts seeded on demineralized bone matrix (DBM), a bone graft substitute material. Together, combined imaging of VEGF expression in living animals and in live cells provided clues about the regulation of VEGF in cells post-bone grafting. These data are particularly significant toward the development of future smart bone graft substitutes.